Multi-track, multi-layer cladding layers of YCF102: an analytical and predictive investigation of geometric characteristics - Xi, Wenchao (2023)
This paper proposes a prediction method of the geometric characteristic parameters of cladding layers with multi-track and multi-layer. YCF102 cladding layers with different number of tracks and layers were laser cladded on the AISI 1045 steel substrate. The changing trend of the geometric characteristic parameters was analyzed by a laser microscope, and the prediction method of clad height, clad width and melt pool depth with the different number of tracks and layers under various processing parameters were proposed respectively. The results show that the increase of the number of tracks and layers lead to the increase of clad height, clad width and melt pool depth. When cladding the sixth layer, the clad width and melt pool depth still show an increasing trend, but the increase rate of melt pool depth slows down. The average residual values between the calculated and measured values of clad height, clad width and melt pool depth are 280.01 μm, 158.90 μm and 8.00 μm respectively, which are only 5.69%, 4.01% and 1.72% of the corresponding measured values. It is indicated that the prediction method is reasonable. The proposed prediction method can be used to predict the geometric characteristic parameters of multi-track and multi-layer cladding layers. The application of the method can effectively save the processing time and cost of the laser cladding repair of machine parts.